Textos e contextos dos problemas de mediação de altura em livros do Renascimento - Cesana, Andressa (2013)
In this work are researched and analyzed texts and contexts in problems dealing with heights measurement in books of the Renaissance Period. The theoretical basis are the ideas of the historians March Bloch and Fernand Braudel, the social, economical and cultural contexts lived by the authors of the analyzed books are considered as to contextualize them in the production process. A long term period was determined for the research - the Renaissance – and the countries studied were Italy and France, where the authors of the analyzed works lived. This is a qualitative research with an historical and documental approach. The central theme of the research is the interpretative approach of the history of the problems dealing with height measurement of objects, considering the problem's enunciation, the languages, the illustrations, the resolutive mathematical processes and the measurements tools presented by each author. There were three mainly distinct contexts of problem solving. Considering the measurement tools used, it was investigated: the “gnomon” on Leon Battista Alberti (1404-1472) the geometric quadrant of Oroncce Finé (1494- 1555) and the folding square of Ottavio Fabri (c. 1544-1612). The construction and use of measurements tools were crucial for the solving process of countless practical problems of each time; the mathematical tools used were basic but sufficient to solve the problems. All authors used basically the same geometric properties in the process of problem solving, and their works reflect the social and cultural context in which they lived and produced them. Each one of them had some relevancy in the society and contributed to the scientific development of that time, writing books based on their problems and needs. This work's results, beyond the joint historical construction around the theme, bring up questions to analyze the relation between the history of mathematics and the mathematical education.